To Craft the Lyric ‘I’ - Hutchinson, Chris (My University, 2025)
Take an X-Acto blade and score the page with one quick downward- slashing stroke while chanting inside your head: Times New Roman, Times New Roman, give me an omen, Times New Roman.
Keywords: poetry; image